INFLUENCE OF INSTITUTIONAL FACTORS ON CIRCULAR ECONOMY PRACTICES IN EMERGING TOURIST DESTINATIONS - Samalgul NASSANBEKOVA (Geo Journal of Tourism and Geosites)
This study examines how key institutions such as policies, incentives and stakeholder collaboration influence the implementation of circular economy initiatives in emerging tourism destinations. Main approach for this study is a case study method with documentary analysis and interviews with key stakeholders using Kazakhstan case. The documentary analysis showed the shortcomings of regulatory framework and adherence to a “planned circularity”. The analysis leads to practical recommendations for policymakers, including the development of comprehensive circular economy guidelines addressing tourism, financial incentives for businesses, infrastructure investment and increased collaboration among stakeholders. This study contributes to the literature by providing a detailed examination of how institutional factors shape circular economy practices in tourism in emerging destinations context. It offers insight into how global circular economy principles can be adapted to local conditions, thereby expanding understanding of the circular economy in different geographic and economic contexts.